Training on Mapping the Potential of Capture Fisheries in Tanjung Pasir Village as an Effort to Develop an Economy Based on Marine Resources - kalfin; Danial; Damar Rais (International Journal of Research in Community Services, 2026)
Tanjung Pasir Village, located on the coast of Tangerang Regency, has significant potential for capture fisheries, but its utilization is still suboptimal. This community service program aims to provide training to the fishermen of Tanjung Pasir Village on the use of efficient and environmentally friendly fishing gear, as well as better management of catch. Through this training, it is expected that fishermen will be able to increase their catch, reduce the negative impact on the environment, and optimize the potential for fisheries product downstream processing. The training results show an increase in fishermen's understanding of the use of environmentally friendly fishing gear and better catch management techniques. This training has also successfully increased fishermen's income, with the average catch value per trip for outboard motorboats reaching 1,406.03 thousand Rupiah, while fishing without a boat only reached 269.37 thousand Rupiah. It is hoped that this program will have a positive impact on the welfare of fishermen and the sustainability of the fisheries sector in Tanjung Pasir Village.